Предмет: Математика,
автор: dad22331
lgx(lg7+lg5)=lg7*lg25
Решите пожалуйста с подробным описанием.
Ответы
Автор ответа:
0
lg5*(lg5+lgx)=lg7*(lg7+lgy)
lgx=lgy*lg5/lg7
Подставим
(lg5)^2+(lg5)^2*lgy/lg7=(lg7)^2+lg7lgy
((lg5)^2/lg7 - lg7)lgy = (lg7)^2 -(lg5)^2
lgy = - lg7
y = 1/7
lgx = -lg7*lg5/lg7
x = 1/5
lgx=lgy*lg5/lg7
Подставим
(lg5)^2+(lg5)^2*lgy/lg7=(lg7)^2+lg7lgy
((lg5)^2/lg7 - lg7)lgy = (lg7)^2 -(lg5)^2
lgy = - lg7
y = 1/7
lgx = -lg7*lg5/lg7
x = 1/5
Похожие вопросы
Предмет: Физика,
автор: liyas06
Предмет: Английский язык,
автор: ustimenkoanna187
Предмет: Математика,
автор: dimavoevodskij21184
Предмет: География,
автор: Эшли1416
Предмет: Литература,
автор: план10